Current Loss Comparison of PWM Operated Transformer-Based and Transformer-Less Inverter - Shahid, Zeeshan; Khan, Sheroz; Alam, A. H. M. Zahirul; Ahmed, Musse Mohamud (IJARECE, 2014)
This paper presents the current and power loss comparison of single-phase 50Hz transformer-less and transformer-based PWM-operated inverters that can be used in applications from small-voltage AC supplies to distributed grid systems or Grid tied systems. The major concern in these inverters is its reliability and power conversion efficiency. The less current loss occur while conversion the more power efficient inverter is. This work obtains 220V 50 Hz AC from a 12V DC input supply voltage (from Solar source or battery). The current loss comparison at each sampling frequency ranging from 1 KHz to 20 KHz for both cases of transformer-based and transformer-less is shown and discussed. Also, are explained circuit configuration and switching pattern for the two configurations of inverters under consideration.